New Algorithm of Tooth Profile Shift Coefficient of Hy-Vo Silent Chain based on Meshing Variation - Lichi An; Yabing Cheng; Wang Gao; Yang Li; Xinyue Li (Jixie chuandong)
Based on the accurate mathematical model， the meshing model of Hy-Vo silent chain with the plate-sprocket subsystem and hob-sprocket subsystem is established. Through building the auxiliary chain plate， a new algorithm to calculate the profile shift coefficient of involute sprocket based on meshing variation for Hy-Vo silent chain transmission system is proposed. Combined with a specific example， the profile shift coefficients are calculated by the new algorithm and the classical algorithm. Based on the virtual machining technology， the actual machining sprocket under different algorithms is obtained. Through measuring the tooth widths under different radius， the tooth profile deviations of actual sprocket are contrastingly analyzed. Based on the multi-body dynamics simulation， the meshing characteristic of the Hy-Vo silent chain transmission systems under different algorithms are analyzed. The results show that the new algorithm could effectively decrease the system performance deviation between the ideal condition and the actual condition. In addition， the new algorithm could not only the calculation results are more accurate， but also applicable to any variation combination of hub tooth angle and sprocket pressure angle.